Occurrence data for native Asian tree species gathered during the APFORGIS project - gaisberger, hannes thomas; Kanchanarak, Tania; Kettle, Christopher J.; Vinceti, Barbara; Josep Serra-Diaz; Jens Svenning; Kandasamy Palanisamy; Gudasalamani Ravikanth; Rekha Warrier; Christian Elloran; Lawrence T. Ramos; Theilade, Ida; et al. (2022)
This dataset has occurrence data of 63 tree species gathered during the APFORGIS project “Establishing an Information System for conserving native tree species and their genetic resources in Asia-Pacific”. It includes information from 24 countries and covers the period since 1952 to 2019.